Key Performance Indicators for Indonesiaâs Small Holder Dairy Farmers - Moran, John (Indonesian Animal Sciences Society, 2008)
This paper presents a series of Key Performance Indicators to help Indonesian farmers identify the possible causes for their poor farm performance and profitability. When assessing farm profitability, these indicators can be split into two types, those diagnosing problems with feeding management and those with herd management. Too many stock on limited land is a common feature on Asian dairy small holdings. Unlike other forms of livestock, milking cows have very high nutrient requirements, therefore high quality forages and purchased concentrates are essential for profitable dairying. Milk income less feed cost is one of the simplest and easy to measure indicators of farm profitability and the quickest to respond to small changes in farm practices. Problems with herd management can be diagnosed using measures such as the proportion of cows actually milking in the herd or their peak yield and persistency of production. There are also simple indicators of herd reproductive performance and of health and growth of young stock that assist in searching for the underlying causes of poor farm profitability. Â Key words: Key performance indicator, dairy farmer, small holder, Indonesian